Immune response of implanted aortic scaffolds decellularized by sonication treatment - Syazwani, N.; Noor Azmi, Azran Azhim; Morimoto, Y.; Furukawa, K.; Ushida, T. (Springer International Publishing, 2014)
Sonication treatment is used in the preparation of scaffold that was able to elicit minimal immune response following implantation. The aim of this study is to investigate the immunologic response of sonicatedly decellularized aortic scaffolds after 7 days of implantation in rat’s subcutaneous tissue. In this study, aorta samples are sonicatedly decellularized at frequency of 170 kHz in the solution of 0.1% and 2% SDS detergents. It was followed by washing process with PBS solution for 5 days. The treated samples are then evaluated histologically by Hematoxylin Eosin (HE) staining. The samples are subcutaneously implanted on the lower right thoracic cavity of Wistar rats. The implants are explanted and evaluated by HE staining. From the histological results, the implanted samples after sonicatedly decellularized with 2% SDS shows minimal immune response, compared to that decellularized with 0.1% SDS detergents. Hence, treated scaffolds that are sonicatedly decellularized with 2% SDS showed great potential as biomedical implants due to its ability in reducing the immune response to a minimal level.